Characteristics of emergency patients admitted to hospital with asthma: A population‐based cohort study in Queensland, Australia. (15th May 2021) - Simunovic, Marko; Erbas, Bircan; Boyle, Justin; Baker, Philip; Davies, Janet M
Abstract: Objective: Patient characteristics with exacerbation of asthma accessing care in the ED who are at risk of hospital admission have not been determined in subtropical climates. The objective of the study was to investigate the spatiotemporal burden of asthma hospital admissions across Queensland (QLD) and model risk factors for asthma hospital admission following an ED visit. Methods: Six years of routinely collected data (2012–2017) from 28 QLD public hospitals were extracted from Queensland Health's Emergency Data Collection. The dataset contained individual, episode‐level ED presentations having asthma‐like diagnoses, and an indicator of hospital admission, including to short‐stay unit (SSU). A generalised additive model was used to examine the risk of asthma hospital admission. Results: Asthma hospital admissions increased from a weekly median of 79 (interquartile range [IQR] 66–99) in 2012 to 104 (IQR 81–135) in 2017. A higher incidence of asthma hospital admission was observed among males (median age 9, IQR 5–32) in childhood and females in adulthood (median age 32, IQR 11–51). Compared to the state capital Brisbane, the odds of asthma hospital admission ranged from 0.48 (95% CI 0.42–0.54) to 1.34 (95%CI 1.21–1.48) in other regions of QLD. Conclusion: Asthma hospital admissions appear to be increasing in QLD, largely driven by utilisation of the SSU admissions for asthma. With large variation in both incidence and proportion admitted across different regions, routinely collected data can in part be used to understand risk factors for asthma‐related hospital admission following an ED presentation and further inform public health policy development. Abstract : The objective of the study was to investigate the spatiotemporal burden of asthma hospital admissions across Queensland (QLD) and model risk factors for asthma hospital admission following an ED visit. Asthma hospital admissions increased from a weekly median of 79 (interquartile range (IQR) 66–99) in 2012 to 104 (IQR 81–135) in 2017. Asthma hospital admissions appear to be increasing in QLD, largely driven by utilisation of the short‐stay unit admissions for asthma. ​